Expectations and monetary policy: Experimental evidence - Oleksiy Kryvtsov; Luba Petersen (Bank of Canada, 2013)
The effectiveness of monetary policy depends, to a large extent, on market expectations of its future actions. In a standard New Keynesian business-cycle model with rational expectations, systematic monetary policy reduces the variance of inflation and the output gap by at least two-thirds. These stabilization benefits can be substantially smaller if expectations are non-rational. We design an economic experiment that identifies the contribution of expectations to macroeconomic stabilization achieved by systematic monetary policy. We find that, despite some non-rational component in expectations formed by experiment participants, monetary policy is quite potent in providing stabilization, reducing macroeconomic variance by roughly half.
Keywords: C9; D84; E3; E52; 330; Business fluctuations and cycles; Monetary policy implementation; Transmission of monetary policy